2020
DOI: 10.1101/2020.05.11.20094854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of goggle-associated harms to health and working status of nurses during management of COVID-19

Abstract: Background To investigate the impact of goggles on their health and clinical practice during management of patients with COVID-19.Methods 231 nurse practitioners were enrolled who worked in isolation region in designated hospitals to admit patients with COVID-19 in China. Demographic data, goggle-associated symptoms and underlying reasons, incidence of medical errors or exposures, the effects of fog in goggles on practice were all collected. Data were stratified and analyzed by age or working experience. Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Similar results were reported by Williams et al (2020), noting a range of physiological discomforts, when wearing PPEs including facemask and eye protection for a prolonged period [ 13 ]. Furthermore, according to the literature, PPE use was associated with discomfort that could affect performance [ 7 , 8 , 21 ]. Thus, there is a need to discuss the consequences of wearing PPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Williams et al (2020), noting a range of physiological discomforts, when wearing PPEs including facemask and eye protection for a prolonged period [ 13 ]. Furthermore, according to the literature, PPE use was associated with discomfort that could affect performance [ 7 , 8 , 21 ]. Thus, there is a need to discuss the consequences of wearing PPE.…”
Section: Discussionmentioning
confidence: 99%
“…Headaches associated with PPE usage have significant and adverse impacts on healthcare workers’ health and performance outcomes. A study contended that most healthcare workers develop exacerbation of their pre-existing headache disorders [ 21 ], which affects their level of work performance. Approximately 91% of respondents in a study exploring the association between headache and PPE stated that increased protective wear usage impacted their control of existing headache issues [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reported discomfort included retroauricular pain (81.8%), chest distress or dyspnea (78.5%), and dizziness or palpitations (42.1%). Another study employed a retrospective cross-sectional design focusing on the relationship between goggles and health in nurses (He et al, 2020). The study revealed that the most common goggle-related symptoms were headaches (79.1%), followed by nausea (46.8%).…”
Section: Miscellaneous Adverse Effectsmentioning
confidence: 99%
“…In a recent survey conducted during SARS-CoV-2 outbreak on 231 nurses in China, use of eye goggles caused headache, skin pressure injury and dizziness in 79%, 66%, and 49% of nurses, respectively. 82.7% of nurses subjectively reported that use of eye goggles negatively impacted their working status, and events of medical errors were reported in 19.5% of nurses wearing goggles (49). Third, foggy goggles may interfere with vision and need frequent adjustment during use, which was reported in 59.7% of nurses in China (49).…”
Section: Discussionmentioning
confidence: 99%
“…82.7% of nurses subjectively reported that use of eye goggles negatively impacted their working status, and events of medical errors were reported in 19.5% of nurses wearing goggles (49). Third, foggy goggles may interfere with vision and need frequent adjustment during use, which was reported in 59.7% of nurses in China (49). The adjustment may lead to increased risk of being infected.…”
Section: Discussionmentioning
confidence: 99%